The Javanese Mysticism of Poet Yasadipura as a Means to Achieve World Peace - Purwadi Purwadi (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2025)
This article explores the mystical philosophy of Javanese poet Kyai Yasadipura and its relevance as a cultural foundation for achieving world peace. The study aims to examine how Javanese mystical values, as expressed in Yasadipura’s literary works, can offer ethical and spiritual insights for contemporary global challenges. Using a hermeneutic qualitative method, this research interprets selected classical texts by Yasadipura through the lens of Javanese theological philosophy, focusing on symbolic expressions, ethical teachings, and metaphysical perspectives rooted in Javanese mysticism (kebatinan). The findings reveal that Yasadipura’s mysticism emphasizes inner harmony (rasa sejati), humility (andap asor), balance between the material and the spiritual (lahir–batin), and unity with the divine (manunggaling kawula lan Gusti). These concepts are not only spiritually profound but also culturally transformative, reflecting a worldview that prioritizes peace through personal enlightenment and collective moral awakening. This study contributes to cultural studies by positioning Javanese mysticism as a viable philosophical framework for global peace education. It also enriches discourses in Javanese Sufism, showing how local Islamic-Javanese synthesis in literature carries universal ethical values. Furthermore, the article offers insights into character education, suggesting that ancestral wisdom, when reinterpreted, can guide the formation of peaceful, empathetic, and spiritually aware individuals in the global era. Yasadipura’s mysticism affirms that cultural heritage can be a powerful tool to promote harmony—not only among individuals, but also across civilizations.